Pengaruh Pola Asuh Orang Tua dan Pembinaan Guru Terhadap Kecerdasan Emosional Siswa di SMP Utama YBM PLN P2B TJBB Gandul Cinere Depok Jawa Barat: Penelitian - Febrifatini; Darwis Hude; Akhmad Shunhaji (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to obtain empirical understanding of the influence of parenting styles and teacher guidance on students’ emotional intelligence. The research problem arises from the crucial role of both family and school in shaping students’ emotional intelligence during early adolescence. This study employed a quantitative approach using the Product Moment correlation technique and multiple linear regression analysis, accompanied by descriptive analysis of questionnaire data distributed to students of SMP Utama YBM PLN P2B TJBB Gandul, Cinere, Depok. The findings revealed that (1) there is a positive and significant influence of parenting style on students’ emotional intelligence, with a t value of 7.733 > 1.989 and a significance level of 0.001 < 0.05, contributing 41.6%; (2) there is a positive and significant influence of teacher guidance on students’ emotional intelligence, with a t value of 6.793 > 1.989 and a significance level of 0.001 < 0.05, contributing 35.5%; and (3) there is a positive and significant simultaneous influence of parenting style and teacher guidance on students’ emotional intelligence, indicated by an F value of 36.851 > 3.110 and a significance level of 0.000 < 0.05. Developing students' emotional intelligence requires collaboration between family parenting patterns and teacher training/mentoring at school.